Causative Pathogens of Endophthalmitis after Intravitreal Anti-VEGF Injection: An International Multicenter Study - Catharina Busch (2019)
© 2019 S. Karger AG, Basel. Purpose: The main objective of this study was to investigate the microbiological spectrum of endophthalmitis after anti-VEGF injections and to compare streptococcal with non-streptococcus-associated cases with regard to baseline characteristics and injection procedure. Methods: Retrospective, international multicenter study of patients with culture-positive endophthalmitis after intravitreal anti-VEGF injection at 17 different retina referral centers. Results: Eighty-three cases with 87 identified pathogens were included. Coagulase-negative staphylococci (59%) and viridans streptococci (15%) were the most frequent pathogens found. The use of postoperative antibiotics and performance of injections in an operating room setting significantly reduced the rate of streptococcus-induced endophthalmitis cases (p = 0.01 for both). Conclusion: We found a statistically significant lower rate of postinjectional local antibiotic therapy and operating room-based procedures among the streptococcus-induced cases compared to cases caused by other organisms.